Emerging market liberalization and the impact on uncovered interest rate parity - Bill Francis; Iftekhar Hasan; Delroy Hunter (Federal Reserve Bank of Atlanta, 2002)
In this paper we make use of the uncovered interest rate parity (UIRP) relationship to examine the extent that the liberalization of emerging financial markets has resulted in the integration of developing countries' currency markets into the international capital market. Previous tests of the impact of liberalization on the integration of emerging markets capital markets into world financial markets are confined to equity markets, ignoring currency markets that arguably are more important in determining the success of financial liberalization. We find that, in general, deviation from UIRP in the emerging markets is systematic in nature and that a significant part of emerging market currency excess returns is attributable to time-varying risk premium. Importantly we also find that these countries' currency deposits provide U.S. (equity) investors the benefits of international diversification. Our results also show that for some markets, liberalization improved (worsened) investors' perception of growth opportunity while reducing (increasing) investors' perception of the probability of financial distress. Finally, while several countries benefited from liberalization and have become more integrated into the world capital market, the experience is country specific.
Keywords: 330; Capital market; Financial markets; Markets